Identification and expression analysis of the lipid phosphate phosphatases gene family reveal their involvement in abiotic stress response in kiwifruit - Yang, Yaming; Chen, Lijuan; Su, Gen; Liu, Fangfang; Zeng, Qiang; Li, Rui; Cha, Guili; Liu, Cuihua; Xing, Libo; Ren, Xiaolin; Ding, Yuduan (Frontiers in Plant Science, 2022)
Lipid phosphate phosphatases (LPP) is a key enzyme in the production and degradation of phosphatidic acid (PA), which plays an important role in plant growth, development, stress resistance and plant hormone response. In this study, 7 members in AcLPP family were identified from the whole genome of kiwifruit, the subcellular localization prediction was mainly on the plasma membrane. Phylogenetic tree analysis showed that the LPP gene of kiwifruit could be divided into four subgroups. Cis-regulatory elements mainly include hormone response elements and abiotic response elements. Go functional annotation revealed that AcLPP gene was closely related to phosphatase/hydrolase activity, phosphorus metabolism and dephosphorylation. 6 AcLPP genes were predicted to be targets of miRNA. The tissue specificity of AcLPP genes indicates that family members participate in the process of fruit development and Post-harvest Ripening, and were specifically expressed in flower and flower bud tissues. qRT-PCR showed that the members of AcLPP genes family may be regulated by ETH, ABA, GA3 and IAA hormone signals. The family members mainly respond to the stress in 4 kinds of stress, salt stress, osmotic stress, cold stress and heat stress. These results can provide a basis and reference for studying the agricultural characteristics of kiwifruit and improving its stress resistance.